(untitled) (IIUC Business Review, 2026)
Merger and acquisition remain popular vehicles for the financial sector. However, despite the extensive body of research on mergers and acquisitions in the financial sector, significant gaps can be observed in understanding the current status, development, and future trends of the issue. The aim of this study is to perform bibliometric analysis and visualize presentations to identify leading journals, countries, regions, institutions, authors, articles, references, number of years, subject areas, and related research questions that have contributed the most to this field of study. The study uses VOS viewer software for a sample of 374 papers from 1994 to 2024. The results illustrate that the number of publications increased from 1994–2014, whereas the number of publications decreased in 2015; however, after 2015, the number of publications again increased. Five leading journals are found, whereas Jens Hagendorff and Dirk Schiereck are the leading authors. Moreover, the United States and the United Kingdom are the leading countries. The results are helpful for obtaining a comprehensive understanding of the current status, progress, and foresight of this field and provide a reference for future studies. IIUC Business Review, Vol.-13, Issue-1, December 2024, pp. 79-100